Ethical approach to the use of immersive technologies. Advance about digitalisation of multilingual programs in the EHEA - Peña-Acuña, Beatriz; Rubio-Alcalá, Fernando David (Frontiers in Virtual Reality, 2024)
This study explores the ethical implications of integrating advanced immersive technologies into education using a snowball documentary methodology, considering multidisciplinary perspectives. Advocating for a holistic approach, it suggests combining legal frameworks, ethical codes, and educational programs centered on core values. The evolving ethical landscape of immersive technologies reveals varied viewpoints among researchers, with some emphasizing concerns and others highlighting advantages. Additionally, some leverage immersive technologies for ethical education in response to emerging challenges. Post-implementation, ethical challenges and norms contribute to the ongoing expansion of the topic. A closer examination identifies nuanced differences and commonalities between immersive technologies and the Metaverse, emphasizing multifaceted considerations. Legal aspects are thoroughly covered in AR, VR, and MxR technologies, while the Metaverse focuses on identity protection. In education, immersive technologies exhibit more developed ethical concerns, underscoring the richness compared to the Metaverse.